Experimental Study on Concrete Incorporating Date Seed As Partial Replacement Of Coarse Aggregates - Ali Raza PALH; Sajjad Ali MANGI; Masroor Ahmed ODHO; Ayaz Ahmed KALHORO (Neutron, 2021)
In the world the most widely used material is concrete. It is the second most consumed substance after water in the world and plays a vital role in infrastructure and private buildings construction. Various waste materials like coconut shells, date seeds, rubber seed shell, palm kernel shells, etc. were studied by various researchers and replaced for coarse aggregate in concrete making. This study attempted to use Date Seeds as partial replacement with coarse aggregate in concrete. The mix design ratio 1:2:4 of cement, fine aggregate and coarse aggregate/date seeds was investigated in this study work only. Total 24 number of Cylinders of diameter and height of 4’×8’ were made. The 0%, 2%, 3% and 4% of Date Seed were replaced with Coarse aggregate. The physical properties of Date Seed, fine aggregate and coarse aggregate were determined. The specific gravity of DS was found to be 1.0 and water absorption was 24% for 48 hours. The bulk density value was 843 kg/m3 which was greater than the previous research works, the fineness modulus of DS, CA & FA were 1.7, 2.18 and 3.08, respectively. Other important thing which was observed during this work that the DS were expanding on absorption of water. The workability of concrete was decreasing as the total surface area of coarser particles was increased. The results of compressive strengths were quite satisfied at 2% & 3% replacement.